Vibrio cholera O1 Ogawa bacteremia with extraintestinal manifestation - Faisal, Ummu Salamah; Zainulabid, Ummu Afeera; Kori, Najma; Periyasamy, Petrick; Khaithir, Tzar Mohd Nizam (Elsevier, 2023)
O1 Ogawa Vibrio cholerae is rarely reported to cause extraintestinal manifestation. Here, we report a case of O1 Ogawa Vibrio cholerae bacteremia with bullous cellulitis of the left leg. The patient acquired the infection through a small skin prick on her leg from contaminated soil that served as an environmental reservoir for Vibrio cholerae.